2017
DOI: 10.1007/s00277-017-3043-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the circulating cell-free DNA marker association with diagnosis and prognostic prediction in patients with lymphoma: a single-center experience

Abstract: Circulating cell-free DNA (ccfDNA) has been shown to be associated with the clinical characteristics and prognosis of cancer patients. Our objective was to assess whether the concentration and integrity index of ccfDNA in plasma may be useful for diagnosing and monitoring the progression of patients with lymphoma. We included plasma samples from 174 lymphoma patients and 80 healthy individuals. The total concentration of ccfDNA was determined using a fluorometry method, and the DNA integrity index (DII), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
2
27
1
2
Order By: Relevance
“…[19][20][21] However, this range of concentration was lower than that of cell-free DNAs in patients with systemic lymphomas (range 100-14 180 ng/mL). 22,23 In our analysis, the MYD88 L265P mutation was not detected in cell-free DNAs by TDS. However, Fontanilles et al recently reported that a variety of somatic mutations specific to CNS tumors, including MYD88 L265P mutation, were detected in cell-free DNAs of PCNSL patients by TDS.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…[19][20][21] However, this range of concentration was lower than that of cell-free DNAs in patients with systemic lymphomas (range 100-14 180 ng/mL). 22,23 In our analysis, the MYD88 L265P mutation was not detected in cell-free DNAs by TDS. However, Fontanilles et al recently reported that a variety of somatic mutations specific to CNS tumors, including MYD88 L265P mutation, were detected in cell-free DNAs of PCNSL patients by TDS.…”
Section: Discussioncontrasting
confidence: 46%
“…Also, the estimated range appears to be higher than that of cell‐free DNA amounts in patients with non‐hematological neoplasms, such as colorectal, lung, and breast cancer (range 0.5‐1980 ng/mL) . However, this range of concentration was lower than that of cell‐free DNAs in patients with systemic lymphomas (range 100‐14 180 ng/mL) …”
Section: Discussionmentioning
confidence: 83%
“…Aside from several physiological states such as pregnancy and physical activity, pathological conditions, including inflammation and autoimmune diseases, may present with elevated cfDNA levels. In cancer, cfDNA levels may be increased up to 1000 ng/mL, which draws attention to an association between cfDNA levels and tumor burden (1,4,8,(10)(11)(12)(13). A previously reported association between age and cfDNA was confirmed in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Cell-free DNA levels were elevated in various hematological disorders. High levels of cfDNA and DNA integrity index represented a lower probability of progression-free survival in diffuse large B cell lymphoma patients (8). Cell-free DNA levels were increased in lymphoma patients and correlated with advanced age and stage, poor prognosis, B symptoms, and lactate dehydrogenase levels (4,6,24).…”
Section: Cfdna: Cell-free Deoxyribonucleic Acidmentioning
confidence: 95%
See 1 more Smart Citation